PROSPECTS FOR SHARIAH-COMPLIANT E-WALLET: ISSUES AND RECOMMENDATIONS - Abdul Muneem; Nor Fahimah Mohd Razif; Abdul Karim Ali; Faizah Hanim Zainuddin; Muhammad Izzul Syahmi Zulkepli (Malaysian Journal of Syariah and Law)
The purpose of this study is to address the concept of e-wallet from a Sharīʿah perspective and its potential Sharīʿah concepts, issues, and challenges and to provide relevant recommendations to overcome those issues and challenges. A qualitative research method is adopted in this study to address the concept of e-wallet, Sharīʿah contracts, issues, and challenges from the Sharīʿah perspective. The collected data of this study is analyzed through an explanatory research approach to fulfill the objectives of this study. The study finds that the Sharīʿah compliant e-wallet is realizable from the Sharīʿah perspective. Although a wadīʿah contract is used for deposit/safekeeping purposes, in this study the concept of qarḍ seems to be a better choice for a contract between user and issuer. However, the cashback and rewards are some issues that arise while using the qarḍ contract since a borrower (issuer) is not allowed to return additional benefits/amount to the lender. In this regard, the study concludes that the benefits of e-wallets either might come from the merchant or the issuer. If those benefits are given by the issuer out of his generosity, and without any condition from the borrower (user), the offer of such benefits will be permissible, on the other hand, if it comes in return for a condition, that will be impermissible. Moreover, the benefits provided by the merchants seem to be permissible due to sale contracts in that transaction. The study also finds that a Sharīʿah compliant e-wallet is required to transfer the funds to a trust account under an Islamic financial institution so that it does not issue an interest for that fund. Additionally, if the fund is allowed to invest, it should be invested in a Sharīʿah compliant investment. The results of this study assist the e-wallet providers to consider Sharīʿah compliance of the e-wallet. In particular, the findings reveal the possibilities of Sharīʿah compliant e-wallet regardless of the issues and challenges it might face. Moreover, it provides room for users who are Islamic fintech enthusiasts. This research presents a deeper insight into wadīʿah and qarḍ contract to be used as underlying contracts between e-wallet providers and users.